IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 20 TAHUN 2012 TENTANG PENGELOLAAN DAN PEMBERDAYAAN PASAR TRADISIONAL (STUDI KASUS PASAR RAU KOTA SERANG) - Sherlinda, Sherlinda; Hartoko, Gatot; Amilia, Rizki (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Traditional markets are a vital component of local economies, yet they often face various management and empowerment challenges. Pasar Rau in Kota Serang is one such market with significant economic potential, but it suffers from issues such as disorganized zoning, poor infrastructure, and weak supervision and trader regulation. In this context, the implementation of the Minister of Home Affairs Regulation No. 20 of 2012 is highly relevant to assess the effectiveness of traditional market management. This study aims to analyze how the policy on traditional market management and empowerment is implemented in Pasar Rau, Kota Serang, using the implementation theory of Van Meter and Van Horn. The theory outlines six key indicators: policy standards and objectives, resources, communication among implementers, characteristics of implementing agencies, socio-economic and political environment, and implementer disposition. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews, field observations, and documentation. Informants included officials from the Department of Industry and Trade (Disperindag), market managers from PT. Pesona Banten Persada, as well as traders and visitors. The findings indicate that the policy implementation is not yet optimal. There are obstacles in human resources, ineffective communication, and resistance from traders due to relocation and limited facilities. The rise of digital platforms such as e-commerce also influences traditional market dynamics. In conclusion, the implementation of market management policies in Pasar Rau still faces significant challenges, both internally and externally. Improvements in coordination, human resource capacity, and participatory approaches are essential for sustainable policy execution.